CERKL is upregulated in cutaneous squamous cell carcinoma and maintains cellular sphingolipids and resistance to oxidative stress. (5th February 2021) - Meyer, J.M.; Lee, E.; Celli, A.; Park, K.; Cho, R.; Lambert, W.; Pitchford, M.; Gordon, M.; Tsai, K.; Cleaver, J.; Arron, S.T.; Mauro, T.M.
Summary: Background: Ceramide kinase‐like protein (CERKL) was originally described in retinal tissue. CERKL has been shown to protect cells from oxidative stress, and mutations in CERKL underlie the inherited disease retinitis pigmentosa. CERKL expression maintains cellular sphingolipids via an unknown mechanism. Objectives: To determine whether CERKL is expressed in epidermis and cutaneous squamous cell carcinoma (cSCC) and whether CERKL expression affects cSCC sphingolipid metabolism and susceptibility to oxidative stress. Methods: CERKL expression was determined by RNA‐Seq, quantitative polymerase chain reaction and immunohistochemistry. CERKL was knocked down in cSCC cells using small interfering RNA. Sphingolipid content was analysed by liquid chromatography–mass spectrometry. Oxidative stress was induced by treatment with H2 O2, and apoptosis was measured using flow cytometry to determine annexin V binding. Results: CERKL mRNA and protein are highly expressed in actinic keratosis and cSCC in comparison with normal epidermis. CERKL is also expressed in metabolically active epithelial cells in normal hair bulbs and sebaceous glands. CERKL knockdown in cultured cSCC cells reduces cellular sphingolipid content and enhances susceptibility to oxidative stress. Conclusions: These findings suggest that CERKL may be important in cSCC progression and could lead to novel strategies for prevention and treatment of cSCC. Abstract : What is already known about this topic? Ceramide kinase‐like protein (CERKL) is thought to protect cells from oxidative stress, and mutations in CERKL underlie the inherited disease retinitis pigmentosa. What does this study add? We found that CERKL is upregulated in cutaneous squamous cell carcinoma (cSCC) compared with normal epidermis. CERKL protects cSCC cells from oxidative stress and maintains cellular sphingolipids. What is the translational message? These findings demonstrate that CERKL may be important in cSCC progression by increasing the resistance of tumours to oxidative stress. Further investigation of CERKL could lead to novel strategies for prevention and treatment of cSCC. Linked Comment:  R.F.L. O'Shaughnessy. Br J Dermatol 2021; 185 :14–15 .